Rational design and crystal structure prediction of ring-fused double-PDI compounds as n-channel organic semiconductors: a DFT study - Debata, Suryakanti; Sahoo, Smruti R; Khatua, Rudranarayan; Sahu, Sridhar (Physical chemistry chemical physics : PCCP, 2021)
In this study, we present an effective molecular design strategy to develop the n-type charge transport characteristics in organic semiconductors, using ring-fused double perylene diimides (DPDIs) as the model compounds. These dimeric-PDIs are formed by joining two separate PDI-units along their bay positions through ring fusion with pyrene, coronene and their N-doped counterparts. The bridging type has a significant steric effect at the annulation positions and controls the molecular geometry, mostly imposing buckling in the structure. The crystal structures of the designed compounds are also theoretically predicted. Thereafter, electronic structure parameters, molecular packing motifs, charge coupling strength and anisotropic mobilities were investigated to understand the charge transport efficiency of these systems. Among all the studied molecules, the 4N-coronene-fused DPDI (DPDI-6) is found to possess a lower LUMO level and a high EA, suggesting air-stable electron injection. Besides, DPDI-6 shows strong intermolecular electron coupling and possesses high electron mobility ( μ e = 5.31 × 10 −2 cm 2 V −1 s −1 ), which is better as compared with the other DPDI-compounds reported here. The DPDIs also possess optical absorption in the UV-visible region, opening up possible applications in organic photovoltaics. Besides, from the non-linear optical (NLO) analysis, DPDI-3 is found to possess the highest first-order hyperpolarizability, which is even better as compared with the reference compound urea, making it a promising candidate for NLO applications. In this study, we present an effective molecular design strategy to develop the n-type charge transport characteristics in organic semiconductors, using ring-fused double perylene diimides (DPDIs) as the model compounds.